Penatalaksanaan Fisioterapi pada Anak Kondisi Tortikolis Sinistra e.c Brachial Palsy dengan Menggunakan Modalitas Infra Red, Massage dan Terapi Latihan di RSUD Bendan Kota Pekalongan - Astini Suci Wulandari; Nur Susanti (LPPM Universitas Pekalongan, 2017)
Torticollis is a state of limited neck movement where the oblique head is tilted and the chin is pointing to the opposite side, which is caused by the shortening of the sternocleidomastoid muscle. In Torticolis Sinistra e.c Brachial Palsy there is a problematic physiotherapy that there is a spasm in the sternocledomastoideus muscle, there is a shortening of the muscle which ultimately leads to a limitation of the scope of joint motion, decreased cervical muscle strength and functional activity of the child is disturbed. In this case the physiotherapy intervention is selected to address the above problems by using Infra Red, Massage and Exercise Therapy.Method approach in this research use descriptive analytic method to know assesment and change that can be known. The research design used was case study design. Research Sites at RSUD Bendan Kota Pekalongan dated 03 to 27 February 2017.Therapeutic results concluded that physiotherapy interventions with Infra Red, Massage and exercise therapy can help problems in childhood conditions Tortikolis e.c Brachial Palsy.